Design of robust broadband beamformers with minimax criterion - Dam, Hai Huyen Heidi; Nordholm, Sven (Kyushu Tokai University, 2015)
Broadband beamformers are known to be sensitive to errors and mismatches in their array elements. This paper proposes a robust minimax beamformer design which takes into account sensor element characteristics. The design formulation minimizes robust integral squared error subject to relaxation constraints on the peak deviation error for the beamformer. The advantage of the proposed formulation is that the design allows a trade-off between the peak deviation error and the sensitivity of the minimax error with respect to variations in sensor element characteristics. This improvement has been achieved with almost no increase in complexity compared with the original minimax problem. Design examples demonstrate that the proposed beamformer is less sensitive with respect to variations in sensor element characteristics when compared to the traditional minimax beamformer with a minor degradation in beamformer performance.